A UV Picture of a Loop Induced Neutrino Mass Model and Its Phenomenological Consequences - Shindou, Tetsuo (Frontiers in Physics, 2019)
In this article, we review several models where tiny neutrino masses are radiatively generated via loop diagrams. In such models, additional scalar fields are often introduced so that the Standard Model Higgs sector is extended.Such an extension results in a rich phenomenology of the model. We briefly discuss such a model and its UV completion to highlight some of its phenomenological consequences.